Evaluation of Field Work Practices of State Vocational High Schools in Malinau Regency - Eldariyanti, Semi; Jabar, Cepi Safruddin Abdul (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to describe Implementation of Field Work Practice (PKL) at State Vocational High School (SMKN) in Malinau Regency and Supporting and inhibiting factors for the implementation of street vendors at the SMKN. This study uses a qualitative approach method of evaluation research type. The research was conducted at SMKN 1 Malinau, SMKN 2 Malinau, and SMK SPP Malinau. The informants in this study consisted of three school principals, three teachers, and three deputy principals for curriculum affairs from the three vocational schools, three students and one IDUKA. Data collection techniques use observation, interviews, and document studies. The data analysis technique uses an interactive model from Sidiq Choiri (2019) with the following levels: 1) Data Collection. 2) Data reduction. 3) Data Presentation. 4) Conclusion Withdrawal/verification. The results of this study show that the implementation of street vendors at SMKN Malinau Regency includes planning cooperation with the Business World and the Industrial World (IDUKA), student preparation, as well as the implementation of monitoring and evaluation during street vendors and f supporting actors for the implementation of street vendors including IDUKA support, active involvement of teachers and principals, and the availability of adequate facilities. The inhibiting factors include budget limitations, local IDUKA limitations, and students' lack of understanding of the world of work.